2001
DOI: 10.1152/ajpheart.2001.281.5.h2143
|View full text |Cite
|
Sign up to set email alerts
|

Role of renin-angiotensin-aldosterone system in salt-sensitive hypertension induced by sensory denervation

Abstract: To define the role of the renin-angiotensin-aldosterone system in a novel salt-sensitive model, neonatal Wistar rats were given capsaicin (50 mg/kg sc) on the first and second days of life. After weaning, male rats were divided into the following six groups and treated for 3 wk with: control + normal sodium diet (CON-NS), CON + high-sodium diet (CON-HS), CON + HS + spironolactone (50 mg x kg(-1) x day(-1), CON-HS-SP), capsaicin pretreatment + NS (CAP-NS), CAP-HS, and CAP-HS-SP. Radioimmunoassay shows that plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data show that selective knockdown of neuronal TRPV1 enhances prohypertensive effects induced by salt loading and that pressor effects of TRPV1 shRNA may be mediated, at least in part, by enhancement of the sympatho-excitatory response. We have previously shown that neonatal degeneration of TRPV1-expressing sensory nerves increased salt sensitivity of arterial pressure as these rats grew into adulthood [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . However, the systemic sensory denervation used in these previous studies precluded us from making conclusions about whether the observed effect was due to the removal of TRPV1 or other proteins co-expressed in the same nerves innervating any specific organs or tissues [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, defining the role of TRPV1-positive sensory nerves in the regulation of blood pressure and salt sensitivity will be useful. We have shown previously that the degeneration of TRPV1-expressing sensory nerves throughout the neonatal body by subcutaneous injection of capsaicin, a selective TRPV1 agonist, leads to increased salt sensitivity of arterial pressure, indicating that TRPV1-positive sensory nerves play a counter-regulatory role against salt-induced increases in blood pressure [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . The underlying mechanism of anti-hypertensive effects of TRPV1 may involve its counter-balancing role against the activation of the renin-angiotensin-aldosterone system [7][8][9] , sympathetic nervous system [10] , endothelin system [11,12] , superoxide generation system [13,14] , and epithelial sodium transporters [15] .…”
Section: Introductionmentioning
confidence: 99%
“…A role for endogenous CGRP herein has not been considered yet. Renal CGRP-containing sensory-motor nerves markedly affect renal function, and they reduce blood pressure increases in response to increased salt intake (Wang et al, 1998;Huang and Wang, 2001). Modulation of these effects by NPY has not been investigated.…”
Section: Efs (2 N Hzmentioning
confidence: 99%
“…We next studied aldosterone and its interaction with the sensory nervous system in the induction of salt-sensitive hypertension, in light of the aforementioned finding that PRA is insufficiently suppressed in neonatally capsaicin-pretreated rats challenged with a salt load [54,55] . Both vehicleand capsaicin-treated rats fed a high-salt diet was given spironolactone, an aldosterone receptor antagonist for 3 weeks.…”
Section: Vr1-positive Sensory Nerves and Increased Salt Sensitivitymentioning
confidence: 99%